Factors Affecting Smoker Visits In Upaya Berhenti Merokok Clinics - Avicena Sakufa Marsanti; Woro Dyah Ayu; Riska Ratnawati (poltekkes kemenkes mataram, 2022)
Upaya Berhenti Merokok Clinic is one of program from public health center which given from government. This clinic contains the smoke-free area and to help smokers who want to quit smoking. The objectives of this analyzing factor that influence the smoker visits in Upaya Berhenti Merokok clinics.In this research, the researcher uses descriptive quantitative research as approach. The method of research is analytical survey while the type of research is cross sectional. Total population of 187 people and using a sample of 126 people.The result of chi-square test shows that was a significant correlation between independet variable was knowledge (p-value = 0,003), intention (p-value = 0,001), attitude (p-value = 0,002), self-motivation (p-value = 0,010), and family support (p-value = 0,014) on smoker visits. And the results of the regressi logistic test most influential variables which are knowledge (p-value = 0.061), attitude (p-value of 0.060), self-motivation (p-value = 0,0153).The most influential variable was attitude with a result of 3,713 meaning that the attitude variable which are the most influential on smokers visit. From this study, the researcher concluded that the great effect on active smoker who visited on Upaya Berhenti Merokok clinics at Tawangrejo primary health center was attitude.